Strategic digitization in currency and payment competition - Cong, Lin William; Mayer, Simon (Journal of Financial Economics, 2025)
We model the competition between digital forms of fiat money and private digital money. Countries digitize their currencies–by upgrading existing or launching new payment systems (including CBDCs)–to compete with foreign fiat currencies and private digital money. A pecking order emerges: less dominant currencies digitize earlier, reflecting a first-mover advantage; dominant currencies delay digitization until they face competition; the weakest currencies forgo digitization. However, delayed digitization allows private digital money to gain widespread adoption, eventually weakening fiat money’s role. We highlight how geopolitical considerations, stablecoins, and interoperability between fiat and private digital money shape the dynamics of currency competition.